Analysis of the Interaction of Zoomorphic Sociorobots with People - Rudenko, V. (My University, 2022)
In this paper, various types, characteristics, and parameters of zoomorphic sociorobots are analyzed. During the analysis, the author set the task to consider the possible areas of application of zoomorphic socio-robots, the results of their influence on humans, as well as their further development.
Keywords: zoomorphic robots; sociorobots